Dynamic Phenotypes and Molecular Mechanisms to Understand the Pathogenesis of Diabetic Nephropathy in Two Widely Used Animal Models of Type 2 Diabetes Mellitus - Liu, Yanfei; Huang, Hui; Gao, Rui; Liu, Yue (Frontiers in Cell and Developmental Biology, 2020)
Objective We aimed to characterize the pathogenesis of diabetic nephropathy (DN) in two commonly used type 2 diabetes mellitus (T2DM) animal models and explore the preliminary molecular mechanisms underlying DN in two models. Methods To verify the effect of hyperglycemia on renal tissue, we observed the cell growth inhibition rate by adding different concentration of glucose to cell supernatant. After that, a chemically-induced T2DM model was established by administering streptozotocin (STZ) to Sprague Dawley (SD) rats in combination with high fat feeding. In addition, a spontaneous T2DM model was established by feeding 8 weeks old KK-Ay mice a high-fat diet during a period of over 20 weeks. Animal body weight, fasting blood glucose (FBG), insulin tolerance, lipid metabolism, renal function, and renal pathology were periodically measured (once every 2 or 4 weeks) over a duration of 20 weeks. At the 12th week, an Affymetrix gene chip assay was performed on the renal tissues extracted from the T2DM animal models and control animals. Through screening for the differentially expressed genes, some key genes were selected for PCR validation. Results High level of glucose could inhibit the growth of kidney cells. Besides, KK-Ay mice were found to have high FBG and abnormal insulin tolerance. Renal dysfunction and pathology were observed at the 4th week following the start of model creation, which increased in severity over the length of the experiment. The T2DM SD rats also showed high FBG, abnormal glucose tolerance and abnormal lipid metabolism, but the renal function and renal pathology changed only slightly within 20 weeks. Gene profiling in animal kidneys and subsequent analyses and validation revealed differentially expressed genes and enriched pathways in DN. Conclusion KK-Ay mice with both high fasting glucose and insulin resistance were more likely to develop diabetic nephropathy than STZ-induced diabetic SD rats with low fasting glucose or only insulin resistance. The KK-Ay mice model showed earlier onset of the typical pathological characteristics associated with T2DM and obvious renal lesions suggestive of kidney damage.